2020
DOI: 10.3389/fmicb.2020.584715
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hg Speciation and Hg Methylation/Demethylation Processes in the Sulfate-Reducing Bacterium Pseudodesulfovibrio hydrargyri: Evidences From HERFD-XANES and Nano-XRF

Abstract: Microorganisms are key players in the transformation of mercury into neurotoxic methylmercury (MeHg). Nevertheless, this mechanism and the opposite MeHg demethylation remain poorly understood. Here, we explored the impact of inorganic mercury (IHg) and MeHg concentrations from 0.05 to 50 μM on the production and degradation of MeHg in two sulfate-reducing bacteria, Pseudodesulfovibrio hydrargyri BerOc1 able to methylate and demethylate mercury and Desulfovibrio desulfuricans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The chosen cysteine and sul de concentrations correspond to the minimal sulfur concentration needed for optimal growth without Hg(II) (Online Resource 2a). The Hg(II) concentrations were chosen from a previous study that showed a maximum of mercury methylation rate at 5 µM of Hg(II) (Isaure et al 2020). Sul de concentrations measured at the end of the growth in the presence of cysteine (0.010 ± 0.003 -0.020 ± 0.005 mM, Interestingly, the Hg(II) methylation potential under non-sul dogenic growth with 0.1 mM sul de was higher than in the other tested conditions, regardless of the Hg(II) concentration (Figure 1a, Online Resource Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chosen cysteine and sul de concentrations correspond to the minimal sulfur concentration needed for optimal growth without Hg(II) (Online Resource 2a). The Hg(II) concentrations were chosen from a previous study that showed a maximum of mercury methylation rate at 5 µM of Hg(II) (Isaure et al 2020). Sul de concentrations measured at the end of the growth in the presence of cysteine (0.010 ± 0.003 -0.020 ± 0.005 mM, Interestingly, the Hg(II) methylation potential under non-sul dogenic growth with 0.1 mM sul de was higher than in the other tested conditions, regardless of the Hg(II) concentration (Figure 1a, Online Resource Table ).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we used P. hydrargyri BerOc1 under three different conditions regarding sul de contents: grown i) under fumarate respiration (non sul dogenic metabolism) in the presence of a wide range of exogenous sul de concentrations, ii) under fumarate respiration in the presence of cysteine and, iii) under sulfate reduction (sul dogenic metabolism). Because Hg methylation depends on Hg(II) concentration (Gilmour et al 2011;Isaure et al 2020), the effect of sul des (added or produced) was also examined at three different Hg(II) concentrations (from nM to µM). Our study provides new insights into the major role of sul des on Hg methylation process at sul de concentrations of environmental relevance, which is important to address the risks of Hg regarding the environmental and the health standpoints on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…A yeast divalent cation transporter DMT1 of participates in the uptake of inorganic mercury [ 56 ]. Research publications on the uptake of inorganic mercury in mercury-methylating Desulfovibrionaceae species and related organisms could guide these future studies [ 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] For significantly improved signal-to-noise ratio for studying biological systems, methods providing high energy resolution fluorescence detected XAS (HERFD-XAS) are constantly gaining importance. [15][16][17][18] In cases where the analyte concentration is extremely low, in nanogram or even picogram range, the use of total reflection X-ray fluorescence XAS (TXRF-XAS) is the variant of choice. 19 Also relevant in the field of biological systems is the advent of X-ray free electron lasers (XFELs) producing ultrashort intense X-ray pulses (pulse widths <100 fs).…”
Section: Introduction Challenges and Perspectivesmentioning
confidence: 99%
“…For significantly improved signal‐to‐noise ratio for studying biological systems, methods providing high energy resolution fluorescence detected XAS (HERFD‐XAS) are constantly gaining importance 15–18 . In cases where the analyte concentration is extremely low, in nanogram or even picogram range, the use of total reflection X‐ray fluorescence XAS (TXRF‐XAS) is the variant of choice 19 …”
Section: Introduction Challenges and Perspectivesmentioning
confidence: 99%